Genetic Mapping of 262 Loci Derived from Expressed Sequences in a Murine Interspecific Cross Using Single-Strand Conformational Polymorphism Analysis - Brady, Kevin P.; Rowe, Lucy B.; Her, Helen; Stevens, Tamara J.; Eppig, Janan; Sussman, Daniel J.; Sikela, James; Beier, David R.

(untitled) (Genome Research, 1997)
We have demonstrated previously that noncoding sequences of genes are a robust source of polymorphisms between mouse species when tested using single-strand conformation polymorphism (SSCP) analysis, and that these polymorphisms are useful for genetic mapping. In this report we demonstrate that presumptive 3′-untranslated region sequence obtained from expressed sequence tags (ESTs) can be analyzed in a similar fashion, and we have used this approach to map 262 loci using an interspecific backcross. These results demonstrate SSCP analysis of genes or ESTs is a simple and efficient means for the genetic localization of transcribed sequences, and is furthermore an approach that is applicable to any system for which there is sufficient sequence polymorphism.